Taro flour usage in wheat flour bread and gluten-free bread: Evaluation of rheological, technological and some nutritional properties - Arici, Muhammet; Ozulku, Gorkem; Kahraman, Burcu; Yildirim, Rusen Metin; Toker, Omer Said (WILEY, 2020)
In the present study, the use of taro flour was investigated for the production wheat flour bread (WFB) and gluten-free bread (GFB). In both types of breads, the substitution level of taro flour was 3.15%, 6.30%, 12.50%, 18.70%, and 25.00%. The results of the study showed that the storage modulus (G ') value was higher than the loss modulus (G '') value in all the bread doughs. Addition of taro flour to wheat flour and gluten-free doughs increased the G ' and G '' values and had strengthening effect on dough structure. Specific volumes of bread samples were ranged from 1.97 to 2.54 ml/g for WFB, from 1.61 to 2.20 ml/g for GFB. Higher resistant starch content was observed in GFB samples than WFB. Dietary fiber content increased significantly as taro flour addition was increased in both formulations (p < .05). Acceptable sensorial properties were achieved with the substitution level of 12.50% for WFB and 18.70% for GFB. Practical Applications Bread has been considered as a central component of human diet for thousands of years. Improving the nutritional quality of bread types without causing quality losses is a major challenge. Moreover, the variety of gluten-free bread needs to be increased in order to provide healthy diet for coeliac disease patients. This study aimed to explore alternative bread formulation by using taro flour. The results showed that taro flour is a contributing ingredient in terms of technological and nutritional properties of both wheat and gluten-free bread. The use of taro flour in bread can provide insights into alternative approaches to extend the bread types to the bakery industry.
Keywords: RESISTANT STARCH; PHYSICOCHEMICAL PROPERTIES; CELIAC-DISEASE; DOUGH RHEOLOGY; DIETARY FIBER; PROTEINS; QUALITY; QUINOA; IMPACT; Engineering; Food Science & Technology